Empirical analysis on economic capital by TailVaR model. (1st January 2014) - Fan, Liu; Ling, Tian
The model of TailVaR was used for analysis of the economic capital in this article. Three empirical works have been basically done, including the measurement of total economic capital, the calculation of economic capital for different lines of business, and the comparison of outcomes. The conclusions from the empirical analysis suggested that different methods of risk management should be implemented in different lines, in which the liability line was emphasised. More indicatively, the economic capital requirement could be reduced due to the effect of 'risk pool' for unexpected loss. Finally, recommendations on the economic capital management were proposed to Chinese insurance companies.